Diary of an oxygen thief eaudiobook - Anonymous (Simon & Schuster Audio, 2016)
Hurt people hurt people. Say there was a novel in which Holden Caulfield was an alcoholic and Lolita was a photographer's assistant and, somehow, they met in Bright Lights, Big City . He's blinded by love. She by ambition. Diary of an Oxygen Thief is an honest, hilarious, and heartrending novel, but above all, a very realistic account of what we do to each other and what we allow to have done to us.